Bilateral and Multilateral Coauthorship and Citation Impact: Patterns in UK and US International Collaboration - Adams, Jonathan; Gurney, Karen A. (Frontiers in Research Metrics and Analytics, 2018)
International collaboration makes up an increasing, high citation-impact share of research output, but the UK’s collaboration with key partners is threatened by its decision to leave the EU. Data show that about 85% of US and UK international collaboration is with only one or two partners, usually among other ‘leading’ research economies. Although highly multi-national research (10 or more authors) is growing more rapidly than total research output, it actually remains scarce (about 1% of all collaboration) among the established research economies. Analysis also shows that the ‘citation bonus’ contributed by international collaboration is in fact both specific and limited; it should therefore be interpreted with some care. For example, citation impact trends look different for two-country and multi-country collaborations involving the same countries. Impact also increases but then plateaus with increasing numbers of partners. Further, we find that massively multi-national papers are of such a different kind that we suggest they should be excluded from standard citation analysis.